Exploring the Neo-Assyrian frontier with Western Iran: the 2015 season at Gird-i Bazar and Qalat-i Dinka - Radner, Karen; Kreppner, Florian Janoscha; Squitieri, Andrea; Kreppner, Florian Janoscha (Peshdar Plain Project Publications, 2016)
The Peshdar district is part of the province of Sulaymaniyah in the Kurdish Autonomous Region of Iraq. The international and interdisciplinary Peshdar Plain Project was inaugurated in 2015 with the goal of investigating the region in the Neo-Assyrian period (9th to 7th century BC). It formed part of the Border March of the Palace Herald which served to negotiate relations with the adjoining client kingdoms in the Zagros, most importantly Mannea (south of Lake Urmiye), ?ubu?kia in the Sardasht Plain and Mu?a?ir in the Rowanduz Plain.Work in 2015 focused on the tiny single-phase site Gird-i Bazar and impressive Qalat-i Dinka, looming on a rocky outcrop high over the river, both part of the Dinka settlement complex. This book presents the results of this first season of field work. Karen Radner offers an analysis of the historical geography of the region on the basis of the textual sources, including the private contract of 725 BC found at Qalat-i Dinka. Mark Altaweel and Anke March provide a geoarchaeological assessment of the Bora Plain while Jessica Giraud presents an evaluation of the Dinka settlement complex based on the results of the survey of the Mission archéologique française du Gouvernorat de Soulaimaniah (MAFGS). Jörg Fassbinder and Andrei A?andulesei discuss the results of their geophysical survey at Gird-i Bazar and Qalat-i Dinka. Tina Greenfield introduces the bioarchaeological sampling strategy. On the basis of the analysis of 666 diagnostic ceramic sherds from key find contexts and by drawing on parallels from the Assyrian heartland and western Iran, Jean-Jacques Herr presents a first assessment of the technical aspects, the fabrics and the shapes of the pottery excavated at Gird-i Bazar. Eleanor Barbanes Wilkinson, Andrea Squitieri and Zahra Hashemi present the small finds from the 2015 excavations